Potential of Indigenous Yeast as a Paraquat Biodegradation Agent in Sumberbrantas, Batu City, Indonesia - Bosha, Mohammed; Abadi, Abdul Latief; Aini, Luqman Qurata (Journal of Tropical Plant Protection, 2022)
Herbicides are a substance or chemical compound used to inhibit growth or kill plants. Herbicides are toxic to weeds or pests as well as cultivated plants. The impact of using the herbicide paraquat causes some microbes to become more resistant and has the potential to be used as a paraquat biodegradation agent. Indigenous yeast is one of the microbes that can be used as a biodegradation agent because it is resistant to the environment. For this reason, This research aimed to investigate the indigenous yeast isolated from the potato field in Sumberbrantas village, Batu City as a bioremediation agent for paraquat herbicide residues.The sampling was carried out in the potato field of Sumberbrantas, Batu City, which in routine maintenance uses a herbicide with active paraquat (1,1 dimethyl -4, 4-bipyridinium dichloride).The isolation results obtained 6 isolates of indigenous yeast which had the potential as biodegradation agents for paraquat. Treatment of yeast isolates MB 1, MB 3, MB 4, MB 6, MB 7, MB 8 at concentrations of 250, 500, 1,000 and 2,000 paraquat were able to survive with a growth percentage of 75-100%. At a concentration of 5,000 Isolated yeast decreased with a growth percentage of 50-75% and MB 1 isolate with 10,000 ppm concentration still survive with a growth percentage of 1-25%. The highest biodegradability ability of yeast was in MB 1. The identification of MB 1 isolates based on molecular characters have similarities in the basic structure of 98.89% with Geotrichum silvicola UFMG 354-228S isolates with accession number NG_0606221.1.